METoclopramide Administration as a Strategy to Overcome MORPHine-ticagrelOr Interaction in PatientS with Unstable Angina PectorIS—The METAMORPHOSIS Trial - Sikora, Joanna; Niezgoda, Piotr; Barańska, Malwina; Buszko, Katarzyna; Skibińska, Natalia; Sroka, Wiktor; Pstrągowski, Krzysztof; Siller-Matula, Jolanta; Bernd, Jilma; Gorog, Diana; Navarese, Eliano Pio; Marszałł, Michał Piotr; Kubica, Jacek (Thrombosis and Haemostasis, 2018)
Extensive search for methods of overcoming morphine-related delay of the absorption and onset of action of oral P2Y12 inhibitors in patients presenting with acute coronary syndrome is on-going. The aim of the trial was to investigate whether metoclopramide co-administration could reduce this delay and improve the pharmacokinetics (PKs) and pharmacodynamics (PDs) of ticagrelor and its active metabolite AR-C124900XX. Plasma concentration of both compounds and platelet reactivity were evaluated in nine pre-defined time points within 6 hours after administration of ticagrelor loading dose. The results of our study show that mean platelet activity within the first hour was noticeably higher in metoclopramide-naive patients. Moreover, ticagrelor mean plasma concentration was significantly higher within the initial four time points (15, 30, 45, 60 minutes) in patients receiving metoclopramide (p = 0.039; p = 0.009; p = 0.005; p = 0.008, respectively). To conclude, the co-administration of metoclopramide in patients presenting with unstable angina and treated with morphine, has a beneficial effect on the PK/PD profile of ticagrelor and its metabolite; however, its impact on ST-elevation myocardial infarction patients requires further investigation.
Keywords: anti-platelet agents; morphine; metoclopramide